Heat load due to LED lighting of in-door strawberry plantation - Chatchawan Chaichana; Parinya Chantrasri; Suwit Wongsila; Suwimon Wicharuck; Thongchai Fongsamootr (Energy Reports, 2020)
This paper investigates heat load due to LED lighting of in-door strawberry plantation. A double-chamber experimental room was designed and constructed at Chiang Mai University, Thailand. There are 180 strawberry plants inside the inner experimental room. Air temperature and moisture of the room can be adjusted using an air conditioner. LED tubes was used to supply light for photosynthesis of the strawberry plant. The air temperature, air moisture, and condensed water from evaporator were measured. Using energy balance and mass balance equations, it was found that, during the use of LED lighting, the condensed water from the experimental room was increased. Calculated heat load of the room were also increased. Approximately 60% of the heat load is from condensation when there is no lighting load. While providing lighting from LED, heat loads from LED and condensation can be almost 100% of total heat load. Increased condensation heat load is the result of evapotranspiration by strawberry plant.
Keywords: 330; Heat load; In-door plantation; LED; Strawberry